IDENTITY CONSTRUCTION BASED ON A COMMUNAL LAYER OF CTI: A CASE ON BOOKSTAGRAM - Witari, Putu Sita (Universitas Bunda Mulia, 2023)
In this digital information age, Instagram, as one of the online social media platforms, has gained more popularity among young generations as a virtual space to express themselves, including their hobby of reading. Since the number of Instagram users who enjoy reading has been growing rapidly, so has the community of readers and book lovers in this virtual space; hence, the terms bookstagram and bookstagrammer have become more well-known. This study investigates how a Bookstagrammer constructs her language identity and online identity on Instagram by analysing the bookstagrammer’s feeds on Instagram and implementing one layer of the Communication Theory of Identity (CTI), the communal identity. Using a method of virtual ethnography, it has been found that the bookstagrammer used English as the predominant language in her posts to connect and expand the interaction with other bookstagrammers worldwide, even though it was not her first language. Alongside, Instagram’s features, such as hashtags and tags in her posts, were her visible efforts to build her identity by actively engaging in the Bookstagram community that supported her to actively participate in the bookstagram community, which eventually enriched the communal identity of bookstagram. A recommendation is offered since the communal layer, and the other three layers of CTI are interconnected and have the potential to bring a more thorough understanding of one’s identity construction on social media.